Sovereign acts : performing race, space, and belonging in Panama and the Canal Zone - Zien, Katherine, 1981- (Critical Caribbean studies., 2017)
"Sovereign Acts investigates the ways that artists, audiences, and activists performed their allegiances to the Panama Canal Zone over a century of US-Panama tensions, in which the Canal Zone's contested sovereignty played a central part. The book examines a series of performances that punctuated the Canal Zone's existence, from its inception in 1903 to its dissolution in 1999, and into the post-occupation present. White US citizens, West Indian labor migrants, and Panamanian artists and activists employed performances - ranging from popular entertainments and patriotic pageants to opera concerts and national theatre - to assert and challenge the Canal Zone's sovereignty, claiming their places in the Zone's physical terrain and representational imaginary. These performances were at once located within the Canal Zone and embedded in transnational flows of US empire, neoliberal capitalism, black internationalism, anticolonial movements, and regional migration. By demonstrating the place of performance in US empire's legal landscape, Sovereign Acts aims to transform our understanding of US imperialism and its aftermath in Panama and what Frank Guridy calls the "US-Caribbean world.""--